PENERAPAN METODE BERMAIN JARI TANGAN DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF PADA ANAK KELAS A DI RAUDHATUL ATHFAL MA’ARIF 01 METRO - Dea, Leli Fertiliana; Setiawan, Agus (Thufuli, 2019)
This study aims to determine whether the application of the method of finger play can develop cognitive abilities in class A children in Raudhatul Athfal Ma’arif 01 Metro. This study used a qualitative approach, with the type of Classroom Action Research (CAR). This study uses a design according to the Kemmis model and Taggart MC which consists of four stages, namely: 1. Planning, 2. Action, 3. Observation, and 4. Reflection ". The subjects of this study were class A children in Raudhatul Athfal Ma’arif 01 Metro 2018/2019 academic year as many as 15 children. The research instrument uses the method of documentation, observation and interviews. Data analysis techniques used quantitative descriptive statistics. The results of the first cycle, indicators of success in cognitive abilities are 60% increased to 80% in cycle II.